Bias Seksisme dalam Penulisan Berita Olahraga: Analisis Wacana Kritis terhadap Represenstasi Atlet Perempuan dalam Asian Games 2018 di Liputan 6.Com - Arief Muliawan (Jurnal ISIP: Jurnal Ilmu Sosial dan Ilmu Politik, 2021)
This article reveals sexist bias in reporting on the 2018 Asian Games event on the online media Liputan6. com. The theoretical basis used is the theory of commodification, gender theory and feminism and representation. The research method takes into account Sara Mills’s critical discourse analysis, with news subjects selected purposively with a sexual bias. The results of the study reveal that the bias occurs through the representation of women who have been reduced in such a way that they only construct female athletes as beautiful aesthetic objects. Women are selected, defined, and displayed as objects and it no longer corresponds to the relevance of sports reporting. This reduction occurs both in texts and in visual image displays.